(untitled) (Prassi Ecdotiche della Modernità Letteraria, 2021)
This essay focuses on the influence exerted by Carlo Porta’s poetry on Siro Carati’s verses. The importance of Carati’s works is due to the fact that he gave new life to the poetry in the Pavese dialect. Carlo Porta, who had claimed the dignity of the Milanese dialect over the Tuscan one, was not only a model for Carati, but indeed an emblematic figure. It emerges from the fact that Carati, in turn, felt the need to claim the literary dignity of the Pavese dialect over the Milanese one, and he did so in a sonnet entitled Sonæt imità dal Porta. From this point of view, it is important to notice that even in the poem I dasgrazi ad Bortlamé Gandion, a free translation of Desgrazzi de Giovannin Bongee, the influence of Porta’s poetry emerges in the form of intertextual echoes. In fact, even in this occasion, Carati absorbed certain features of Porta’s poetry and ultimately created a new, original text.